2011
DOI: 10.1002/cjce.20397
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental analyses of anti‐fouling and heat transfer in the heat exchanger with circulating fluidized bed

Abstract: Fluidized bed type heat exchangers are known to increase the heat transfer and prevent the fouling. For proper design of circulating fluidized bed heat exchanger it is important to know the effect of design and operating parameters on the bed to the wall heat transfer coefficient. The numerical analysis by using CFX 11.0 commercial code was done for proper design of the heat exchanger. The present experimental studies were also conducted to investigate the effects of circulating solid particles on the characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Moreover, the CFBHT was also able to prevent fouling by salt crystals, otherwise known as ice crystallization fouling. Kang et al [12] reported a favorable effect of the CFBHT on fouling. They used Fe 2 O 3 , one of the well-known fouling particles, with and without Al beads as circulating particles to operate the CFBHT.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the CFBHT was also able to prevent fouling by salt crystals, otherwise known as ice crystallization fouling. Kang et al [12] reported a favorable effect of the CFBHT on fouling. They used Fe 2 O 3 , one of the well-known fouling particles, with and without Al beads as circulating particles to operate the CFBHT.…”
Section: Introductionmentioning
confidence: 99%
“…Solid particles (metallic, non-metallic, or polymeric) of millimeter of micrometer sizes have been used by several previous works [1][2][3] to enhance the heat transfer. Under certain conditions this method gives reasonable heat transfer enhancement.…”
Section: Introductionmentioning
confidence: 99%